PENINGKATAN PERFORMA BATERAI AIR LAUT MENGGUNAKAN Cu-Zn BERDASARKAN LUAS PENAMPANG ELEKTRODA - irfan irfan; Abdul Muis Prasetia (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2022)
Seawater in Indonesia has considerable potential when used as a source of renewable energy. As it is known that sea water generally contains elements or levels of salt dissolved in it. Due to the presence of these elements or levels of salt, seawater has the potential to produce electrical energy. This is the reason why researchers want to do more in-depth research on this seawater battery. As it is known that several previous studies have conducted experiments using different methods in each research conducted. In this study, we will use several methods that have been there previously aimed at getting an increase in electrical energy that will be generated from marine batteries. This study uses a cross-section of electrodes in the form of copper and zinc by comparing several methods to get a seawater battery design that suits your needs. In this study, the seawater battery used pure seawater and without using an amplifier circuit or voltage booster. With a voltage that can be generated in each 1 cell, which is between 0.78 V and 0.82 V. Overall, this seawater battery has 10 cells arranged in series with each 1 cell consisting of 5 pairs of copper and zinc electrodes arranged in parallel.